2022
DOI: 10.1097/ncc.0000000000001159
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian Nurses’ Perspectives of Spirituality and Spiritual Care

Abstract: Background: Spirituality is considered one of the main aspects of wholesome care for human beings. Spirituality is a multidimensional concept and has several definitions in the literature. Most of the studies concerning spirituality were conducted in Western cultures and the Middle East; however, there are a limited number of studies regarding spirituality in Jordan. Objective: The aim of this study was to explore Jordanian nurses' perspectives on spirituality and spiritual care in a palliative care unit in 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Literature suggests increasing the competencies of healthcare personnel to address and support patients and family caregivers psychosocially and spiritually [39]. However, studies carried out in various countries reported that the spiritual care competency of health personnel was below the desired level, nurses feel inadequate in delivering spiritual care and need training [35,[40][41][42]. Similarly, in this study, we determined that nurses perceive themselves as inadequate in delivering spiritual care and want to receive training.…”
Section: Barriersmentioning
confidence: 77%
See 1 more Smart Citation
“…Literature suggests increasing the competencies of healthcare personnel to address and support patients and family caregivers psychosocially and spiritually [39]. However, studies carried out in various countries reported that the spiritual care competency of health personnel was below the desired level, nurses feel inadequate in delivering spiritual care and need training [35,[40][41][42]. Similarly, in this study, we determined that nurses perceive themselves as inadequate in delivering spiritual care and want to receive training.…”
Section: Barriersmentioning
confidence: 77%
“…The nurses' mean age was 35.8 ± 6.73 years (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), their working experience in the PCU ranged from 5 months to 7 years, and their overall work experience ranged from 5 to 23 years. 54.5% of the family caregivers were female, with a mean age of 43.09 ± 10.11 , while their patients' hospitalization time ranged from 3 to 92 days.…”
Section: Resultsmentioning
confidence: 99%